STUDI EKSPERIMENTAL PENGARUH TIPE BANTALAN YANG DIGUNAKAN, PERUBAHAN KAPASITAS DAN HEAD POMPA SENTRIFUGAL SATU TINGKAT TERHADAP PRILAKU VIBRASINYA - Ikhwansyah Isranuri; Zulkifli Lubis; Abd. Wahid Simangunsong; Zuhri Zahra (Jurnal Dinamis, 2009)
ABSTRACTThis paper is a report of the results of a research on the influence of bearing type due to the vibration characteristic of a single-stage centrifugal pump. The pump used in this research is a centrifugal pump with maximum head of nine meters, maximum capacity of 3.5 liter/second and power of 746 Watt. Poly Vinyl Carbon (PVC) pipe is used in suction and discharge pipes. The suction pipe of 50 mm in diameter and 1.73 meters long which are equipped with valve and pipe support. The discharge pipe of 50 mm in diameter and 4.4 meters long which are equipped with valve, water meter, manometer and pipe support. The static head of the system is 1.13 m and the total head of system is three meters. The vibration characteristic test is observed and analyzed through vibration parameters consisting of displacement, velocity and acceleration. Vibration measurement is range from the head three meters to seven meters and the vibration response is measured by Vibrometer Analog VM-3314A. P-01 and P-02 are the measurement points on pump and measured in axial, vertical and horizontal direction. Deep groove ball bearing as the original pump bearing, cylindrical bearing, and tapered bearing are types of bearing which used in this research. These two types of bearing are mostly found in field to be applied, when the original pump bearing are replaced for maintenance or life time reason. The result of research reveals that the highest displacement in horizontal direction occurred at P-02 with head of three meters, capacity of 1.3 liter/second when ball bearing is used in the pump with value of displacement 37.125 m. Tapered bearing produces the lowest displacement compared to ball bearing or cylindrical bearing with the displacement value of 27.1 m in the same condition.Key words: Vibration; Bearing; Centrifugal pump